The concept of monadas and its applications in contemporary critical discourse (Journal of the College of Basic Education, 2023)
The clear acceleration in contemporary critical discourse systems and their shifts from contextual action to reading actions based on the continuous modernization processes in the tools of the critical process and the methods of analysis of the creative achievement, led to the representation of the critical system as a form of interdependence between several areas and fields of knowledge such as: philosophy, language, literature Art....etc.Here, the overlap in the systems of contemporary criticism led to the manifestation of each approach as a carrier of several conceptual manifestations and references, which interacted with it and transmitted to it its communicative tools with both cosmic and creative realities. In revealing the components of the critical system and how the critical approach operates on the intellectual complex and building it into the functional unit represented by the apparent form (matter) based on the intellectual unit representing the process of working on the basic relationships in the creative achievement, and thus, drawing the lines of operation of the elements within the details of consciousness and its relational and communicative transformations.Where the researcher sees the need to update critical discourse by referring to philosophical questions and using them to come up with other questions, which are more comprehensive and may be able to connect with the intellectual data of the postmodern stage.The research contained three chapters:1. The first chapter: the methodological framework, including the research problem, the importance of the research, the research objectives, and defining the terms.2. The second chapter: the theoretical framework, which includes two sections: the first is the aesthetic development of the two monada concepts. The second topic: The Monada in the light of the contemporary critical reading strategy.3. Chapter Three: Research Procedures: Where the research chose a theoretical sample in its adoption of the deconstructive approach as an intentional sample, the aim of this is to analyze the critical approach in the light of the premises of the Monada concept.4. Chapter Four: Broadcast Results and Sources.